Mecanismos de geração de massa para neutrinos - Lima, Dibartolomei Antônio Pereira de (2010)
Studied in this work two mechanisms for generating mass for the neutrinos which are extentions of the SM. The first chapter is a presentation of the Standard Model with its contents and properties. The second chapter discusses an extension with the insertion of the right-handed neutrino component that implies in Dirac s massive particle and a Majorana mass term, which combines with the first term to result in Type I Seesaw. In The third chapter the extension is made by adition of a triplet of scalars that generates to a Majorana mass term for neutrinos leading to Type II Seesaw. In The last chapter we study the effective operator at low energies that generates as a more elegant and short mass for neutrinos associate without which the fundamental theory that leads to that operator.